Analisis Faktor Ganjaran Yang Mempengaruhi Kinerja Karyawan Pada Kasus Aksi Mogok Nasional Buruh - Fauzi, Nurul Baridah; Rahmadhani, Lailani Octavia; Winarsih; Murdiana, Velda (HUMANUS : Jurnal Sosiohumaniora Nusantara, 2024)
A national labor action is a form of protest carried out by workers to demand their rights that are considered unfulfilled. The national labor action that occurred in 2023 in Indonesia had a significant impact on various sectors, including the industrial sector. One of the impacts that arose was the decline in employee performance in several affected companies. The research method used is the descriptive qualitative method. Descriptive qualitative research aims to describe and illustrate existing phenomena. Thus, it can be concluded that the workers are disappointed with the injustice in terms of the wages given, they feel that the wages/salaries given are not proportional to the performance they put out. This reason is a factor in the workers’ insistence on getting an increase in their wages. Overall, the workers’ national labor action was based on dissatisfaction with the wages given to workers in Indonesia, giving rise to the national labor action. In this context, the calculation of inflation, economic growth, and the current need for a decent living are important factors that must be considered in raising wage increases for workers. These factors can also affect the work stress and welfare of the workers.  The speech action this time conveyed two demands, namely the revision of the DKI UMP from 3.6% to 15% and the implementation of the minimum wage under the Jakarta Labor Law.